For positive a , b and c , find the minimum value of a b c ( a + b ) 2 + ( a + b + 4 c ) 2 ( a + b + c ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
(Calvin's rant about minimum)
When finding the minimum of a function, we have to show
As pointed out by Mark, this solution only does 1, but not 2.
You have used the AM/GM inequality five times. To achieve the minimum value of 1 0 0 , using your argument, you need to show that all these inequalities can be equalities at the same time (for example when a = b = 2 , c = 1 .
Since the quantity you want to minimize is homogeneous in a , b , c , you could add the restriction a + b + c = 1 without loss of generality, and then you simply need to minimize a b c ( 1 − c ) 2 + ( 1 + 3 c ) 2 a + b + c = 1 , a , b , c > 0 One application of the AM/GM inequality will show that this is minimized when a = b = 2 1 ( 1 − c ) , so all you have to do is minimize c ( 1 − c ) 2 4 [ ( 1 − c ) 2 + ( 1 + 3 c ) 2 ] 0 < c < 1 which is minimized when c = 5 1 .
Log in to reply
Hmmm. Since the expression is minimized when a = b = c , this looks like it can be solved using UVW method . But for some reason I couldn't seem to finish it off...
On the other hand, UVW seems to be more complicated than the standard AM/GM approach that you used. So I guess UVW is not desired here.
Agreed! And I added my usual rant above.
Another approach to finding the equality condition via the existing proof is to track what needs to hold at each stage of inequality. In this proof, we need a + b = a + 2 c = b + 2 c in the first paragraph, and 2 c = b = a = a b , a = b = 2 c in the second paragraph. Since we can find a solution set (like ( 2 , 2 , 1 ) ), hence equality can hold througout.
It would suit the problem more if it was considered in Algebra.
I used Titu's Lemma and AM - GM Inequality ...But I got 5 4 ∗ 4 1 / 3
EDITED : I didn't look for the equality case.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Applying the Arithmetic Mean Geometric Mean Inequality
By the AM-GM inequality , we have ( a + b ) 2 + ( a + b + 4 c ) 2 = ( a + b ) 2 + ( ( a + 2 c ) + ( b + 2 c ) ) 2 ⩾ ( 2 a b ) 2 + ( 2 2 a c + 2 2 b c ) 2 = 4 a b + 8 a c + 8 b c + 1 6 c a b .
Therefore,
a b c ( a + b ) 2 + ( a + b + 4 c ) 2 ( a + b + c ) ⩾ a b c 4 a b + 8 a c + 8 b c + 1 6 c a b ( a + b + c ) = ( c 4 + b 8 + a 8 + a b 1 6 ) ( a + b + c ) = 8 ( 2 c 1 + b 1 + a 1 + a b 1 + a b 1 ) ( 2 a + 2 a + 2 b + 2 b + c ) ⩾ 8 ( 5 5 2 a 2 b 2 c 1 ) ( 5 5 2 4 a 2 b 2 c ) = 1 0 0 .
Thus, the minimum value required is 1 0 0 .